Manual Handling in Aged Care: Impact of Environment-related Interventions on Mobility - Robyn L. Coman; Carlo Caponecchia; Andrew S. McIntosh (Elsevier, 2018)
The manual handling of people (MHP) is known to be associated with high incidence of musculoskeletal disorders for aged care staff. Environment-related MHP interventions, such as appropriate seated heights to aid sit-to-stand transfers, can reduce staff injury while improving the patient's mobility. Promoting patient mobility within the manual handling interaction is an endorsed MHP risk control intervention strategy. This article provides a narrative review of the types of MHP environmental controls that can improve mobility, as well as the extent to which these environmental controls are considered in MHP risk management and assessment tools. Although a range of possible environmental interventions exist, current tools only consider these in a limited manner. Development of an assessment tool that more comprehensively covers environmental strategies in MHP risk management could help reduce staff injury and improve resident mobility through auditing existing practices and guiding the design of new and refurbished aged care facilities. Keywords: Activities of daily living, Assistive technology, Manual handling of people, Residential aged care, Role of the environment in the manual handling of people